Early Physiotherapy Rehabilitation after Lower Segment Cesarean Section Delivery - Nair, Tushara; Mehta, Chakshu; Kumar, G.P. (Medical Science: Trends and Innovations Vol. 12, 2025)
Lower segment cesarean section (LSCS) is one of the common modes of delivery carried out nowadays to prevent complications during a normal delivery. It is a life-saving surgery for the mother and the child. LSCS is a surgical procedure wherein the abdominal wall and the uterus are incised to deliver the child. The recovery of a patient after LSCS is difficult and slow compared to that of a normal delivery due to mobility restrictions due by the scar and the incision. The functional capacity of the patient also gets limited due to incisional pain. Physiotherapy is a useful tool to hasten and enhance the recovery of such patients. Generalized physiotherapy protocols for patients after LSCS are available in the literature. However, there is a lack of evidence of personalized protocols to date. Hence, this chapter aims to explain how to form a personalized early physiotherapeutic rehabilitation for LSCS patients.